Helical Radiotherapy in Early Laryngeal Cancers Could Lead to Excess Local Recurrence: Lessons From a Phase II Prospective Study. Issue 2 (February 2020) - Chatterjee, S.; Mallick, I.; Chakraborty, S.; Prasath, S.; Arunsingh, M.; Achari, R.B.; Arun, B.; Nallathambi, C.; Pattatheyil, A.; Sen, S.
Abstract: Aims: A prospective study was conducted to investigate the feasibility and efficacy of carotid-sparing intensity-modulated radiotherapy (CSIMRT) in early glottic cancers (EGC). Materials and methods: Eighteen patients underwent CSIMRT using helical tomotherapy to a dose of 55 Gy/20 fractions/4 weeks. Carotid intimal thickness (CIT) at prespecified carotid levels was measured using B-mode ultrasound at 6, 18 and 36 months. Serial changes in CIT were also measured in a control prospective cohort of 18 patients with head and neck cancers receiving bilateral neck nodal radiation over the same time period (54–60 Gy/30 fraction/6 weeks). The outcomes of 18 patients undergoing CSIMRT were compared against a retrospective consecutive cohort of 41 patients with EGC to confirm comparable local control. Results: No significant CIT differences were identified between patients undergoing CSIMRT versus the control group. However, four patients in the CSIMRT group had a local recurrence between 8 and 39 months. In all patients the epicentre of the recurrence was noted at the anterior part of the larynx. The 5-year local recurrence-free survival was 75.1% (95% confidence interval 56.6–99.7%). By contrast, in the group of EGC patients treated without carotid sparing, local recurrence was noted only in a single patient (patient treated with helical tomotherapy) and the 5-year local recurrence-free survival was 97.1% (95% confidence interval 91.8–100%) (Log-rank P = 0.01). Conclusion: We failed to show the safety of CSIMRT using helical tomotherapy in this population of EGC patients. Use of CSIMRT also did not translate into a substantial reduction in CIT until 36 months. Use of CSIMRT using rotational arc techniques such as helical tomotherapy may be associated with a greater risk of local recurrence due to intrafractional motion interplay effects. Highlights: Phase II study of carotid sparing Helical Tomotherapy in early glottic cancers. Safety was not demonstrated as there was an increased risk of local recurrence. No reduction in the increase of carotid intimal thickness at 36 months was identified. Caution should be used when using VMAT for carotid sparing in this setting. Internal organ motion, treatment time and helical field width may affect control of early glottic cancers.